Analisis Kebijakan Perpustakaan SMA Negeri 1 Sei Rampah Terhadap Hak Cipta Untuk Mencegah Resiko Plagiarisme - Vinna Rahmawati; Yusniah (UPT Perpustakaan UIN Alauddin Makassar, 2024)
In efforts to encourage and maintain the results of work to accelerate the development of national intelligence, it is important to feel the existence of legal protection for copyright. This study aims to analyze the library policy of SMA Negeri 1 Sei Rampah on copyright to prevent the risk of plagiarism in the school environment. This type of research is descriptive research with a qualitative approach. Data collection techniques in this study are observation and interviews. Data analysis used in this study is the Miles and Huberman model analysis called the